PENYUSUNAN FORMAT RENCANA USAHA BAGI PENGUSAHA KULINER DI KAWASAN CENDANA BANJARMASIN - Mohammad Zainul; Rahmi Widyanti (Universitas Islam kalimantan MAB, 2016)
Entrepreneurial development in Indonesia is very small, amounts to 0.18% of the total population. Ironic considering the number of available potential in Indonesia's earth (natural resources), so abundant to be a good product. The slow development of entrepreneurs in Indonesia is influenced by how much attention the government to its citizens. Look at our government today. Do they invite to use the product in the country? we can take the example of one of the government's policies, import salt, chili, rice etc. Is it appropriate for the State of Indonesia as an agricultural country with the dawn of rice cultivation such imports?. Government attention is needed to empower people to improve the entrepreneurial spirit. Especially in developing informal business communities of the culinary business. However, it is also the role of public institutions and universities by providing socialization and counseling, in order to accelerate the empowerment felt by the public and obtain maximum benefit in managing the business.In an effort to increase business profits, culinary entrepreneurs need to be given knowledge about the preparation of the business plan format.Keywords: Business Plan Format, Entrepreneur Culinary